Religious transformation in South Asia the meanings of conversion in colonial Punjab - Harding, Christopher, 1978- (Oxford historical monographs., 2008)
Exploring the phenomenon of mass conversion to Christianity amongst oppressed rural peoples in late colonial India 'Religious Transformation in South Asia' looks at what lay behind the social and religious aspirations of converts and mission personnel.